Environmental Factors Impacting Bone-Relevant Chemokines - Smith, Justin T.; Schneider, Andrew D.; Katchko, Karina M.; Yun, Chawon; Hsu, Erin L. (Frontiers in Endocrinology, 2017)
Chemokines play an important role in normal bone physiology and the pathophysiology of many bone diseases. The recent increased focus on the individual roles of this class of proteins in the context of bone has shown that members of the two major chemokine subfamilies—CC and CXC—support or promote the formation of new bone and the remodeling of existing bone in response to a myriad of stimuli. These chemotactic molecules are crucial in orchestrating appropriate cellular homing, osteoblastogenesis, and osteoclastogenesis during normal bone repair. Bone healing is a complex cascade of carefully-regulated processes, including inflammation, progenitor cell recruitment, differentiation, and remodeling. The extensive role of chemokines in these processes and the known links between environmental contaminants and chemokine expression/activity leaves ample opportunity for disruption of bone healing by environmental factors. However, despite increased clinical awareness, the potential impact of many of these environmental factors on bone-related chemokines is still ill-defined. A great deal of focus has been placed on environmental exposure to various endocrine disruptors (bisphenol A, phthalate esters, etc.), volatile organic compounds (VOC), dioxins, and heavy metals, though mainly in other tissues. Awareness of the impact of other less well-studied bone toxicants, such as fluoride, mold & fungal toxins, asbestos, and chlorine, is also reviewed. In many cases, the literature on these toxins in osteogenic models is lacking. However, research focused on their effects in other tissues and cell lines provides clues for where future resources could be best utilized. This review aims to serve as a current and exhaustive resource detailing the known links between several classes of high-interest environmental pollutants and their interaction with the chemokines relevant to bone healing.